2014
DOI: 10.1371/journal.pntd.0003269
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Infections among Haitian and Expatriate Non-governmental Organization Workers — Léogane and Port-au-Prince, Haiti, 2012

Abstract: In October 2012, the Haitian Ministry of Health and the US CDC were notified of 25 recent dengue cases, confirmed by rapid diagnostic tests (RDTs), among non-governmental organization (NGO) workers. We conducted a serosurvey among NGO workers in Léogane and Port-au-Prince to determine the extent of and risk factors for dengue virus infection. Of the total 776 staff from targeted NGOs in Léogane and Port-au-Prince, 173 (22%; 52 expatriates and 121 Haitians) participated. Anti-dengue virus (DENV) IgM antibody wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Little information is available regarding the incidence of dengue in Kenya as only one comparable seroincidence survey has been conducted during an ongoing outbreak, and disease surveillance has been limited [ 11 – 18 ]. Our attack rate was similar to that found (14% IgM anti-DENV positive) during a dengue outbreak affecting refugee camps in neighboring Somalia almost 10 years earlier [ 33 ], and comparable to the rate of recent dengue infection during an outbreak investigation in Haiti which used the same methods [ 34 ]. The only other serosurvey was conducted in western Kenya using banked, paired serum samples from 354 afebrile children aged 12–47 months [ 12 ], which identified three anti-DENV IgG seroconversions in ~1 year period for an estimated incidence of 850 DENV infections per 100,000 persons.…”
Section: Discussionsupporting
confidence: 87%
“…Little information is available regarding the incidence of dengue in Kenya as only one comparable seroincidence survey has been conducted during an ongoing outbreak, and disease surveillance has been limited [ 11 – 18 ]. Our attack rate was similar to that found (14% IgM anti-DENV positive) during a dengue outbreak affecting refugee camps in neighboring Somalia almost 10 years earlier [ 33 ], and comparable to the rate of recent dengue infection during an outbreak investigation in Haiti which used the same methods [ 34 ]. The only other serosurvey was conducted in western Kenya using banked, paired serum samples from 354 afebrile children aged 12–47 months [ 12 ], which identified three anti-DENV IgG seroconversions in ~1 year period for an estimated incidence of 850 DENV infections per 100,000 persons.…”
Section: Discussionsupporting
confidence: 87%
“…These findings complement other surveys conducted in nearby Leogane, where 100% of middle-aged adults (mean age 33) had serological markers of DENV exposure, as well as in Port-au-Prince, where, by 3 years of age, 65% of the study participants were seropositive, with all four DENV serotypes identified. 8,22 In 2001, Halstead and others found that 85% of the population had antibodies to two or more DENV serotypes estimated an annual SCR of 30%; which is nearly identical to the seroprevalence and SCR estimated by the current study. 10 Though the SCR suggests hyperendemic transmission of DENV, it was notable that the seroprevalence saturated around 80-85% and never approached 100%.…”
Section: Discussionsupporting
confidence: 82%
“…7 Previous studies have identified the presence of DENV antibodies in native Haitians; however, most recent studies have focused on active infections and/or seroconversion in nongovernment organization workers or missionaries to Haiti; thus, the disease burden of DENV in the native population remains to be adequately characterized. [8][9][10] Furthermore, even though cases of WNV have been reported in Haiti and WNV has been detected in birds and mosquitos from the Dominican Republic, no active surveillance for WNV has taken place for over a decade. [11][12][13] Given the frequent reports of undifferentiated febrile illness, abundance of both Aedes and Culex mosquito vectors, and absence of a national arbovirus surveillance system, a cross-sectional seroepidemiological survey was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging infections, such as pathologies not present in a territory but of import due to migrations and higher mobility among workers (for example, cases of dengue and Zika from South America or avian influenza from China), must be taken into account for the purposes of proper health surveillance [60,61].…”
Section: Discussionmentioning
confidence: 99%